Extending an Almost Complete Pair of Matrices to a Complete Triple - Sheng Chen; Chao Xia (The Scientific World Journal)
Motivated by the concept of complete pairs, which was introduced by Krein and Langer, we present the concepts of an almost complete pair of matrices and a complete triple of matrices. It is proved that an almost complete pair of matrices can be extended to a complete triple. An application of the result to differential equations is also given.